Greco Arabic Concept of Uterine Prolapse (Nute Rehm) - Farzana, M.U.Z.N.; Shiffa, M.S.M.; Tharique, I.A.; Fahamiya, N. (Directorate General of Indian Systems of Medicine, India, 2015)
Genital prolapse in women is not a condition to modern times, modern diet or modern living...
Keywords: Unani Medicine; Humoral theory; Uterine prolapsed; akhlaat arba